PENGARUH PENGAPURAN DAN PEMUPUKAN FOSFOR PADA TANAH YANG SERING TERGENANG TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) - Bukhari Bukhari; Nuryulsen Safridar; Rudi Fadli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The purpose of this study were: (1) To determine the effect of dolomite lime and phosphorus fertilization on soils that were often inundated on the growth and yield of peanuts, (2) to determine the interaction between these two factors on the growth and production of peanuts in soils that were often inundated. The experimental design used in this study was